Potencial da Farinha de Bagaço de Maçã no tratamento dietoterápico de pessoas idosas Ponta Grossa 2007 - Coelho, Laylla Marques (2007)
The industrialization of the apple, in particular of the juice, generates in the processing, as main residue, or by-product, the pomace, for which the concern in managing it adequately must be enters the priorities of the processing industries. The composition physicist-chemistry of the apple pomace flour in this study presented 43% of staple fibers in dry base. The studies on staple fibers demonstrate that they show a hypocholesterolemic action, therefore reduce the digestion and the absorption of the dietary lipids, increases the fecal eliminate acid biliary and steroid the neutral ones, increases the production of acid of short chain in colon and diminishes the percentage of biliary elementary schools in bile. The objective of this study was to develop an alimentary product for an assay of cost evaluation/benefit, with group of aged in confinement, being used 30 g/day apple pomace flour, supplemented in products daily. The research counted on the free participation of 31 citizens that had carried through laboratories examinations of glucose, cholesterol and fractions and triglycerides and had answered questions on intestinal functioning. The averages of the results of total cholesterol and LDLcholesterol shown that in the group it was controlled did not have reduction during the intervention with the apple pomace flour and in the group in intervention of the apple pomace flour in its feeding had reduction of up to 14,71% and 14,69% respectively. Proving that the apple pomace flour can constitute potential alternative source of the alimentary fiber for the food formularization and demonstrates to trend in the reduction of the total cholesterol and LDL-cholesterol.